1989
DOI: 10.1002/hep.1840100213
|View full text |Cite
|
Sign up to set email alerts
|

Natural course and response to interferon of chronic hepatitis B accompanied by antibody to hepatitis B e antigen

Abstract: The course of chronic hepatitis B was studied in 30 patients who had antibody to hepatitis e antigen and hepatitis B virus DNA in the serum and hepatitis B core antigen in the liver. Over a 2-year period, no patient experienced a sustained spontaneous remission of disease, and follow-up liver histology revealed worsening of the disease in four patients. After 2 years of observation, 24 patients were allocated randomly to one of two groups: 12 patients served as untreated controls and 12 received recombinant hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
114
1
5

Year Published

1996
1996
2005
2005

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(122 citation statements)
references
References 14 publications
2
114
1
5
Order By: Relevance
“…8,10,19,20 Other studies have shown higher on-treatment and sustained response rates. [30][31][32] Sustained response to lamivudine posttreatment is currently under evaluation.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…8,10,19,20 Other studies have shown higher on-treatment and sustained response rates. [30][31][32] Sustained response to lamivudine posttreatment is currently under evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Sustained suppression of HBV replication and normalization of ALT may be associated with important clinical benefits in patients with precore mutant chronic hepatitis B who undergo frequent fluctuations in levels of viremia and serum ALT. 10 Previous studies have shown that the persistence of detectable serum levels of HBV DNA and marked fluctuations in serum ALT are associated with an increased risk of cirrhosis. 11,12 Brunetto et al 10 studied the natural course of chronic hepatitis B in anti-HBe-positive patients and showed spontaneous remissions of disease to be infrequent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations